2011
DOI: 10.1002/jor.21530
|View full text |Cite
|
Sign up to set email alerts
|

Suture anchor versus screw fixation for greater tuberosity fractures of the humerus—a biomechanical study

Abstract: Suture anchors and screws are commonly used for fixation of humeral greater tuberosity (GT) fractures in either arthroscopic or open surgeries, but no biomechanical studies have been performed to compare the strength of fixation constructs using these two implants. This cadaveric study aimed to compare the biomechanical strength of three different fixation constructs in the management of GT fractures: Double-Row Suture Anchor Fixation (DR); Suture-Bridge Technique using suture anchors and knotless suture ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
2
47
0
2
Order By: Relevance
“…These have excellent bone quality, which is representative of young human bone. For example, our specimens were able to withstand the loads to failure reported in previous cadaveric GT biomechanical studies (263 N and 370 N at 3 mm and 5 mm of displacement respectively for suture bridge double row fixation) (Braunstein et al, 2007;Ishak et al, 2006;Lin et al, 2012). However, it may not serve as an adequate model for older, osteoporotic bone.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These have excellent bone quality, which is representative of young human bone. For example, our specimens were able to withstand the loads to failure reported in previous cadaveric GT biomechanical studies (263 N and 370 N at 3 mm and 5 mm of displacement respectively for suture bridge double row fixation) (Braunstein et al, 2007;Ishak et al, 2006;Lin et al, 2012). However, it may not serve as an adequate model for older, osteoporotic bone.…”
Section: Discussionmentioning
confidence: 75%
“…Previous biomechanical studies have evaluated fixation for this splittype fracture (Braunstein et al, 2007;Ishak et al, 2006;Lin et al, 2012) and have consistently demonstrated the inferiority of screw fixation compared to Double row and tension band in terms of resistance to displacement (load at 3 and 5 mm) and load to failure. Two separate studies demonstrated the superiority of the tension band and double-row fixation techniques but no study has directly compared the two.…”
Section: Introductionmentioning
confidence: 97%
“…5,12,16,19 A previous study compared the biomechanical strength of 3 common fixation constructs of these 2 materials and showed that constructs using suture anchors had better biomechanical strength. 22 However, no biomechanical studies have been conducted to investigate the influence of shoulder abduction position on the biomechanical properties of these 3 fixation constructs.…”
mentioning
confidence: 99%
“…The authors conclude that suture anchor constructs provide stronger fixation than screws for GT fractures. 17 Overall, outcomes and biomechanical studies show that arthroscopic-assisted GT fixation is a safe, effective, and reliable alternative to open fixation for fractures of the GT of the humerus. Long-term studies should be performed to assess outcomes, and comparative studies should be performed to elucidate the advantages and disadvantages of open versus arthroscopic-assisted procedures.…”
Section: Discussionmentioning
confidence: 92%
“…15 Most recently, Liao et al 16 published the largest series in the literature directly comparing arthroscopic to open fixation for GT fractures in 26 versus 53 patients, respectively; the authors found no clinically significant difference in time to union, complications, or outcomes scores between the groups. 16 Lin et al 17 compared double-row suture anchor fixation (DR), suture-bridge technique using knotless Relying on arthroscopic visualization without the addition of fluoroscopy may lead to malreduction suture anchor fixation (SB), and two-screw fixation (TS) techniques. Mean force of cyclic loading to create 3 mm of displacement was significantly different among all 3 groups (SB > DR > TS).…”
Section: Discussionmentioning
confidence: 99%